Being 40 or younger is an independent risk factor for relapse in operable breast cancer patients: The Saudi Arabia experience - Alshabanah Mohamed; Al Malik Osama; Tulbah Asma; Alsayed Adher; Al-Zahrani Ali; Ajarim Dahish; Dermime Said; Elkum Naser; Ezzat Adnan; Al-Tweigeri Taher (BMC Cancer, 2007)
Abstract Background Breast cancer in young Saudi women is a crucial problem. According to the 2002 annual report of Saudi National Cancer Registry, breast cancers that developed before the age of 40 comprise 26.4% of all female breast cancers comparing to 6.5% in the USA. Breast cancer in young patients is often associated with a poorer prognosis, but there has been a scarcity of published data in the Middle East population. Methods Total of 867 breast cancer patients seen at King Faisal Specialist Hospital & Research Centre (KFSH&RC) between 1986 and 2002 were reviewed. Patients were divided in two age groups: ≤ 40 years and above 40 years. The clinicopathological characteristics and treatment outcomes were compared between younger and older age groups. Results Median age at presentation was 45 years. A total of 288 (33.2%) patients were aged ≤ 40 years. Hormone receptors were positive in 69% of patients 40 and 78.2% of patients above 40 (p = 0.009). There was a significantly higher incidence of grade III tumor in younger patients compared to older patients (p = 0.0006). Stage, tumor size, lymphatic/vascular invasion, number of nodes and axillary lymph node status, did not differ significantly between the two age groups. Younger patients had a greater probability of recurrence at all time periods (p = 0.035). Young age had a negative impact on survival of patients with positive axillary lymph nodes (p = 0.030) but not on survival of patients with negative lymph nodes (p = 0.695). Stage, tumor size, nodal status and hormonal receptors had negative impact on survival. Adjuvant chemotherapy was administered to 87.9% of younger and 65.6% of older patients (p < 0.0001). In terms of hormone therapy, the proportion of tamoxifen treated patients was significantly lower in young age group (p < 0.0001). No significant difference in radiation therapy between the two groups. Conclusion Young age (≤ 40) is an independent risk factor for relapse in operable Saudi breast cancer patients. The fundamental biology of young age breast cancer patients needs to be elucidated.